Quality of Air Status in Selected Traffic Junction Points of Bengaluru City - A Case Study - Dr. S Harinath, Pavithra P, Puspha Lumina (International Journal of Advanced Science and Technology, 2020)
The Air is important to breathe for all living beings, without presence of air it highly difficult to survive on the earth. The present study carried out in selected areas of the Bengaluru city, those areas are have most of the working time busy with high traffic volume. The areas covered with the study of Particulate Matter 10 and 2.5. The status of study areas showing polluted one due to excess of particulate matters due to emission of exhaust smoke by vehicles, and also other activities carrying in the surrounding areas. Keywords: Particulate matter, Electronic devise.